Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.2 - Solving Quadratic Equations by Completing the Square - Exercise Set: 37

Answer

$y=1$

Work Step by Step

$\dfrac{1}{2}y^{2}=y-\dfrac{1}{2}$ Multiply the whole equation by $2$ to avoid working with fractions: $2\Big(\dfrac{1}{2}y^{2}=y-\dfrac{1}{2}\Big)$ $y^{2}=2y-1$ Take all terms to the left side of the equation: $y^{2}-2y+1=0$ Use the quadratic formula to solve this equation. The formula is $y=\dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}$. Here, $a=1$, $b=-2$ and $c=1$. Substitute: $y=\dfrac{-(-2)\pm\sqrt{(-2)^{2}-4(1)(1)}}{2(1)}=\dfrac{2\pm\sqrt{4-4}}{2}=...$ $...=\dfrac{2\pm\sqrt{0}}{2}=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.